1955
DOI: 10.1084/jem.102.3.291
|View full text |Cite
|
Sign up to set email alerts
|

The Requirement of Ovalbumin for the Growth of Group a Hemolytic Streptococcus in a Synthetic Medium

Abstract: Crystalline ovalbumin, when heated under controlled conditions, promoted growth of Streptococcus hemolyticus in a synthetic medium. A similar activation of albumin also was produced by ultraviolet irradiation or by shaking under nitrogen. Untreated albumin failed to permit growth under the same conditions. The activity of treated albumin was destroyed by aeration or by reaction with iodoacetate. The data suggest that the activity of ovalbumin for the streptococcus depends on the presence of "exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1959
1959
1983
1983

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Later, Sprince and Woolley reported the requirement of a factor, subsequently termed strepogenin (22), for growth in a casein hydrolysate basal medium (28). Two partially defined media that were described by Slade and co-workers contained a nondialyzable polypeptide from pancreatic digest of casein (19) or heated ovalbumin (20) in an otherwise chemically defined medium (CDM). Ogburn et al (18), while studying the production of protease, were able to obtain a low yield of organisms from a chemically defined medium after sequential reduction of casein hydrolysate.…”
mentioning
confidence: 99%
“…Later, Sprince and Woolley reported the requirement of a factor, subsequently termed strepogenin (22), for growth in a casein hydrolysate basal medium (28). Two partially defined media that were described by Slade and co-workers contained a nondialyzable polypeptide from pancreatic digest of casein (19) or heated ovalbumin (20) in an otherwise chemically defined medium (CDM). Ogburn et al (18), while studying the production of protease, were able to obtain a low yield of organisms from a chemically defined medium after sequential reduction of casein hydrolysate.…”
mentioning
confidence: 99%
“…Such media that support the growth of various serotypes of group A streptococci have been formulated previously (Zampieri et al, 1960;Ginsburg & Grossowicz, 1957;Ogburn et al, 1958;Mickelson, 1964;Davies et al, 1968;Van de Rijn & Kessler, 1980). Thus peptides or proteins were not absolute requirements for growth as contended by Slade & Slamp (1955).…”
Section: Discussionmentioning
confidence: 92%
“…The chemical and environmental factors that influence the formation of streptolysin 0 and other streptococcal products have been so far poorly documented. Previous investigations have shown that, in spite of good bacterial growth, streptolysin 0 production could be greatly affected by the nature of protein hydrolysates, glucose concentration or reducing agents of culture media (Slade & Knox, 1950 ;Slade & Slamp, 1955 ;Boszormknyi et al, 1967 ;Fuvessy et al, 1967 ;Holm & Falsen, 1967 ;Holm & Moller, 1971 ;Ozegowski et al, 1981). It was not always clear whether the low levels of streptolysin 0 (or its absence sometimes) in certain media were due to the inhibition of its synthesis, or release or to: (i) toxin denaturation as this protein is relatively labile and hydrophobic (Alouf, 1980); (ii) inactivation by cholesterol present in complex media ingredients; (iii) degradation by streptococcal proteinase, the production of which is greatly stimulated by glucose, certain peptones, yeast extract and pH below 6.7 (Cohen, 1969;Ozegowski et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Not only can the substrate concentrations be controlled by regulating the rate at which fresh medium is fed to the culture, but deleterious metabolic end products are maintained at constant and relatively low levels. Although preformed peptides have been implicated in growth and protein production of the streptococci (8,20,26), the results with the continuous culture technique show that no peptides are necessary for either growth of streptococci or M protein production. The one possible Hematin Yes 6.0 X 10-4 a 9.3 X 10-3 Yes 6.0 X exception noted was subsequent to repeated freezing and thawing, when complex medium was required during the lag phase.…”
Section: Discussionmentioning
confidence: 97%
“…loss of M protein (26). Fox and Krampitz (8) reported that nonproliferating streptococci required peptides for production of M protein.…”
mentioning
confidence: 99%